Hydrogen/methanol production in a novel multifunctional reactor with in situ adsorption: modeling and optimization. (16th August 2013) - Bayat, M.; Hamidi, M.; Dehghani, Z.; Rahimpour, M. R.; Shariati, A.
SUMMARY This work proposes a novel multifunctional reactor for simultaneous production of hydrogen and methanol in which zeolite 4A is considered as water adsorbent. For this purpose, in the exothermic side of the proposed configuration, a gas‐flowing solid‐fixed bed reactor (GFSFBR) is used. The remarkable advantage of GFSFBR over the conventional sorption‐enhanced reaction process is the continuous adsorbent regeneration in this novel reactor. MR takes the advantages of adsorption and couple technique simultaneously. The new configuration is designed as a double pipe reactor where highly exothermic methanol synthesis reactions in the exothermic side are coupled with dehydrogenation of cyclohexane. A one‐dimensional, steady‐state heterogeneous model is used to simulate the proposed reactor configuration. Simulation result demonstrates that selective adsorption of water in the exothermic side leads to 22.5%, 9.85% and 7.1% enhancement in methanol, benzene and hydrogen production, respectively, compared with the zero solid mass flux condition. Subsequently, the aforementioned reactor is optimized using differential evolution algorithm to maximize the hydrogen mole fraction in the endothermic side as well as the methanol yield in the exothermic side. Copyright © 2013 John Wiley & Sons, Ltd.